INSTITUTIONALIZATION OF PERFORMANCE MANAGEMENT SYSTEM IN A MALAYSIAN LOCAL GOVERNMENT FROM THE PERSPECTIVE OF NEW INSTITUTIONAL SOCIOLOGY - Hasbolah, Farhana; Alwi, Norhayati Mohd; Mohamad, Muslim Har Sani (UI Scholars Hub, 2018)
The purpose of this paper is to examine the process of institutionalizing and implementing Key Performance Indicators (KPIs) in a Malaysian local government (LG). New Institutional Sociology (NIS) is used to understand the various institutional pressures faced by the organization during the development and implementation process of KPIs. An interpretive case-study strategy was applied. A total of 22 interviews have been conducted with the top management of the LG. The findings suggest that the evolution of the Performance Management System (PMS) in the LG was a result of the directions of government through the Government Transformation Programme (GTP) and is still in its infancy stage. Although the LG has adopted the contemporary PMS, the old PMS; Annual Work Target (AWT) is still the dominant PMS. The KPIs initiative was considered as secondary PMS; therefore, it became as a complementary tool to the existing system. The study also discovered that the KPIs had brought several changes to the staff, departments, and the organization itself. The outcome of the KPIs' implementation, however, could not be studied. The research outcome has contributed to the existing performance management literature especially in the development of PMS within the Malaysian context by exploring the development and implementation of KPIs in an LG as well as the organizational changes within the organization.